ChemInform Abstract: Alternate Method for the Synthesis of Six‐Membered Carbocycles with Five Stereocenters: 1, 2, 3, 4, 6‐Pentasubstituted‐4‐hydroxy‐cyclohexanes. Issue 7 (January 2016) - Gezegen, Hayreddin; Ceylan, Mustafa
Abstract: A simple method for the chemoselective synthesis of multisubstituted cyclohexane derivatives from ketones and aldehydes is presented.